Development of the Layout Concept of a Small-Dimensioned Mobile Robot With Increased Accessibility - Yevsieiev, V.; Uskov, S. (International Scientific Unity, 2024)
The relevance of the development of new concepts of layouts of small-sized mobile robots with increased cross-country ability is due to a number of modern challenges and trends in various fields. First, in the context of increasing urbanization and the increasing number of urban objects, such as steps, stairs, and uneven surfaces, high-traffic mobile robots can be effectively used to perform tasks in a variety of environments. Secondly, in connection with the expansion of the application of robotics in autonomous systems, for example, in the field of transport, medicine and research, the appearance of small-sized mobile robots becomes an integral part of this development. The ability to penetrate hard-to-reach places and move in conditions of limited space allows them to perform tasks that are difficult to solve using traditional methods. Third, in the context of increasing requirements for the efficiency and speed of task performance in various fields, including production and maintenance, the evelopment of high-traffic mobile robot layouts can greatly facilitate routine operations and ensure more efficient use of resources. Summarizing, the development of new concepts of layouts of small-sized mobile robots, oriented to increased traffic, meets the requirements of modern society and opens up wide opportunities for improving autonomous systems in various industries.
Keywords: Small-Dimensioned Mobile Robots; increased traffic